(untitled) (Journal of Computational Mathematics, 2000)
In this paper we present a family of parallel iterations of order m+2 with parameter m=0,1,... for simultaneous finding all zeros of a polynomial without evaluation of derivatives, which includes the well known Weierstrass-Durand-Dochev-Kerner and Börsch-Supan-Nourein iterations as the special cases for m=0 and m=1, respectively. Some numerical examples are given.